The lived experience of withdrawal from Selective Serotonin Reuptake Inhibitor (SSRI) antidepressants: A qualitative interview study - Raqeeb Mahmood; Vuokko Wallace; Professor Nicola Wiles; Professor David Kessler; Katherine S. Button; Graeme Fairchild (Health Expectations)
Abstract Background Our knowledge of the broader impacts of antidepressant withdrawal, beyond physical side effects, is limited. Further research is needed to investigate the lived experiences of withdrawal, to aid clinicians on how to guide patients through the process. Aim To explore antidepressant users’ experiences and views on the withdrawal process and how it affected their quality of life across multiple life domains. Design and Setting We conducted in‐depth qualitative interviews with 20 individuals from the community who had attempted to withdraw from Serotonin Reuptake Inhibitor antidepressants in the past year. Method Semi‐structured interviews were conducted online. A topic guide was used to ensure consistency across interviews. The interviews were audio‐recorded and transcribed verbatim and analysed using inductive reflexive thematic analysis. Results Five themes were generated. The first highlighted the challenges of managing the release from emotional blunting and cognitive suppression following antidepressant discontinuation. The second related to the negative impact of withdrawal on close relationships and social interactions. The third showed that concurrent with negative physical symptoms, there was a positive impact on health (exercise was reported by some as a coping mechanism). The fourth theme focused on support from GPs and families, emphasising the importance of mental health literacy in others. The final theme underscored the importance of gradual and flexible tapering in enabling a manageable withdrawal experience, and the consideration of timing. Conclusion The lived experience of withdrawal significantly impacts individuals’ well‐being. Participants emphasised that withdrawal is not just about physical side effects but also affects their emotional, cognitive, and social functioning. Patient and Public Involvement (PPI) Eight people attended individual online meetings to share their experiences of antidepressant withdrawal to help inform the study design and recruitment strategy. Insights from these meetings informed the development of the topic guide. Questions about GP involvement, family relationships, and mood and thinking changes were included based on this PPI work. This ensured the inclusion of topics important to antidepressant users and facilitated the researcher's questioning during the interviews.